ORIENTALISM IN THE TALE OF GENJI’S TRANSLATIONS AS WORLD LITERATURE - Dewi Christa Kobis (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2019)
This paper is to discuss the “Orientalism” in The Tale of Genji as world literature through the translations of The Tale of Genji that had been translated into English by the Westerns. The popularity of The Tale of Genji cannot be separated from the important role of the translation. The English translations of The Tale of Genji had become a tool for the people surround the World to enjoy reading The Tale of Genji although they cannot speak or read Japanese. We cannot take lightly the role of translation. Regarding to the translation issue, it is also important to know closely about the translators’ perspective towards The Tale of Genji. Since the major translators of The Tale of Genji are Western, it is imperative to know Westerns’ perspectives towards Easterns since The Tale of Genji came from Asian. With the purpose to resolve this case, the analysis of this paper uses Orientalism as its theoretical concept in examining the Westerns’ perspective towards The Tale of Genji through the translation. This paper also examines how the translations of The Tale of Genji could be easily received as the world literature.